2019
DOI: 10.1002/adom.201901042
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimaging and Nanospectroscopy of Polaritons with Time Resolved s‐SNOM

Abstract: The development of electronics and photonics is entering a new era of ultrahigh speed sensing, data processing, and telecommunication. The carrier frequencies of the next‐generation electronic devices inevitably extend beyond radio frequencies, marching toward the nominally photonics‐dominated territories, e.g., terahertz and beyond. As a result, electronic and photonic techniques naturally merge and seek common ground. At the forefront of this technical trend is the field of polaritonics, where polaritons are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 148 publications
(225 reference statements)
0
28
0
Order By: Relevance
“…When molecular vibrational modes are strongly coupled to the cavity modes, they form hybridized quasiparticles–molecular vibrational polaritons. [ 17–40 ] Using a coupled dual‐cavity polariton platform, [ 17 ] we previously demonstrated that nonlinear interactions in the system can be delocalized, through exciting the dark state populations. However, it is insufficient to realize coherence transfer because, unlike dark states, polariton coherences are much shorter lived and are vulnerable to solvent fluctuations across spaces.…”
Section: Introductionmentioning
confidence: 99%
“…When molecular vibrational modes are strongly coupled to the cavity modes, they form hybridized quasiparticles–molecular vibrational polaritons. [ 17–40 ] Using a coupled dual‐cavity polariton platform, [ 17 ] we previously demonstrated that nonlinear interactions in the system can be delocalized, through exciting the dark state populations. However, it is insufficient to realize coherence transfer because, unlike dark states, polariton coherences are much shorter lived and are vulnerable to solvent fluctuations across spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear [352][353][354] and quantum [355][356][357][358][359] properties of plasmonic structures are in the vanguard of current research. Plasmon polaritons can be controlled at femto-second timescales [67,267,[360][361][362][363] enabling access to novel physics and applications [364,365]. Plasmonic waveguides have been incorporated with light-emitting materials, paving the way for integrated plasmonic and photonic structures [366].…”
Section: Dn Basov Et Al: Polariton Panoramamentioning
confidence: 99%
“…Researchers have branched out to explore the possibilities offered by other terahertz sources, both pulsed and continuous-wave [98][99][100]. Meanwhile, the first report of time-resolved pump-probe experiments coupled to an apertureless s-SNOM [101] has inspired interest in studying terahertz photophysics with both femtosecond temporal resolution and nanometer-scale spatial resolution [102,103]. Several other variations of these experiments have been reported.…”
Section: Thz Near-field Imagingmentioning
confidence: 99%